Between Political Administration and Administrative Policy: A reading in the book My Story of Sheikh Mohammed bin Rashid Al Maktoum - Alkharji, Najeya Ali Rashid (Journal of Humanities & Social Sciences, 2022)
The study selected the book (My Story) by Sheikh Mohammed bin Rashid Al Maktoum, to study the levels of form and content thereof. In terms of form, dealt with it as a work that belongs to the art of biography, and it lies between the general biography and the literature of memoirs, and thus ends with its categorical position. The Study brought up to the message content of the book that aimed to deliver which revolves around the necessity of separating the administrative work from those who specialize in management, not politicians, then he reveals through his experiences the extent of his connection with the renaissance of Dubai, emphasizing in different occasions that he and his father laid the base for the success of the development experience in Dubai. The researcher managed to summarize elements of this experience by placing it in relation to books specialized in modern management in more than one feature, the most important of which is that it relied on what specialists today call participatory management that makes the participants in any work responsible for this work, and also relied on the youth component in creation of future leaders by providing them with full opportunities to make decisions and assume responsibility. The research concluded that there are environmental and human components that all contributed to forming the personality of Mohammed bin Rashid Al Maktoum as his grandfather. His father, his mother, the extended desert, and the galloping horses all made of him a leader who did not know the impossible and who believed only in work and sustainable growth.